Safety assessment and protection of monuments located in caves - a case study from the city of Volos, Greece - Loupasakis, C.; Nikolaou, N. (Bulletin of the Geological Society of Greece, 2007)
The holy shrine ofPanagia (Saint Maria) Goritsis is located in a cave on the outer limits of the city of Volos, on the coastline. The stability problems caused by the loosening of the rockmass and the expansion of the joints generated issues about the safety of the numerous worshippers visiting the church every day. The cave is located into the Middle Triassic - Upper Jurassic marbles of the Pelagonian zone. The fragmentation of the rockmass along the two faults intersecting the slope until the coastline, combined with the weathering action of waves led to the formation of the cave. Although the action of the waves was cut of by the construction of the narthex and the surrounding buildings, the stability problems of the cave are intensified by the dynamic loading of the roof. The ceiling of cave is located 1 to 3 metres under the national road and the railway line connecting Volos with Agia. The selection of the proper support measures was complicated. The limited space, the small depth and most of all the religious and the historical value of the cave led to the selection of light support measures combined with the imposition of restriction for the reduction of the dynamic and the static loading